Simulation tools of DC-DC converters for power electronics education - Canesin, Carlos A. [UNESP]; Gonçalves, Flávio A. S. [UNESP]; Sampaio, Leonardo P. [UNESP] (My University, 2009)
This paper presents interactive simulation tools to support the enhancement of power electronics education considering DC to DC converters. These interactive tools make use of the benefits of Java language to provide a dynamic and interactive visualization of simulations in steady-state for idealized non-isolated DC to DC converters. Additionally, this paper discusses the features and the usage of the interactive educational tools to serve as a first design tool for the laboratory experiments in the power electronics courses. In this way, some results were confronted with a well-known simulator package and with experimental results in order to validate the developed interactive simulation tools.
Keywords: Converter circuit; DC-DC converters; Education Methodology; Education Tool; Simulation